2021
DOI: 10.1016/j.radi.2021.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Phenomena of radiography science - A scoping review

Abstract: Introduction:The purpose of the study is to clarify the domain of radiography science. The main goal of science is building knowledge and developing ideas and theories that explain, predict, understand or interpret the phenomena investigated. Each discipline has its own perspective to view and study the phenomena of interest. The disciplinary perspective enables researchers in radiography science to reason and conceptualize phenomena, but it can also restrict them. The aim of this review was to investigate phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Instead of an open first round, we used a scoping review as the starting point of our study. In an earlier study (Törnroos et al, 2021), we identified 117 research interests for radiography science. They formed the basis of the first‐round questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of an open first round, we used a scoping review as the starting point of our study. In an earlier study (Törnroos et al, 2021), we identified 117 research interests for radiography science. They formed the basis of the first‐round questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Research priorities in radiography science identified F I G U R E 1 Description of the Delphi process. The two steps comprising the top row (scoping review) conducted prior to the current study have been reported in Törnroos et al (2021) 3 | RESULTS…”
Section: Forty-one Items Reach Consensusmentioning
confidence: 99%
“…The existence of two distinct research pillars, namely imaging technology and patient care, [1] and three areas (diagnostic, therapeutic and nuclear medicine) with many specialisations and variations globally (sonography, mammography, cross-sectional radiography etc.) make professional recognition even more challenging [4] . Even the professional title varies amongst countries, with Radiographer for the European Federation of Radiographer Societies (EFRS) or Techicien en Radiologie Medicale in Switzerland or Manipulateur d'electroradiologie medicale in France, Funding: This study did not receive any specific grant from funding agencies in the public, commercial, or notfor-profit sectors.…”
Section: A Profession In the Makingmentioning
confidence: 99%
“…[3] Medical Imaging Technologist and Radiation Therapist in Australia, or Radiologic Technologist in United States of America making harder to be identify as a profession. Recognition requires to build up the necessary research capacity, to facilitate the continuous development of specific knowledge and the understanding of the associated clinical implications that, combined with clinical expertise, can lead to evidence-based practice ensuring the quality of the provided healthcare services [4][5][6] .…”
Section: A Profession In the Makingmentioning
confidence: 99%
“…The concept of radiography is not straightforward nor easy to comprehend, and there are different interpretations depending on the scientific perspective [4,5]. The variety in interpretations can cause contradictions and lack of clarity depending on the scientific context, discipline and viewpoint.…”
Section: Introductionmentioning
confidence: 99%